Is Vulvovaginal Lichen Planus Associated With Squamous Cell Carcinoma?. Issue 2 (April 2018) - Day, Tania; Otton, Geoff; Jaaback, Ken; Weigner, Julie; Scurry, James
Abstract : Objective: The aim of the study was to assess for the presence of vulvar lichen planus (LP) in association with human papillomavirus (HPV)–independent squamous cell carcinoma (SCC). Materials and Methods: We performed a clinicohistopathologic review of consecutive vulvectomies and wide local excisions for HPV-independent vulvar or vaginal SCC from 2007 to 2017. Data collected included site of SCC, adjacent precursor lesions and dermatoses, dermatologic treatment, and outcome. Results: There were 43 cases of primary HPV-independent vulvar SCC treated by excision, but no vaginal cancers. Eighteen women (42%) had a preoperative diagnosis of lichen sclerosus (LS); none had a diagnosis of LP. Topical corticosteroids were prescribed in 19 (44%) of 43, with 4 women placed on maintenance therapy. Tumors arose from the labia minora, labia majora, and periclitoris, but not from vestibule or perianus. On histopathological review, LS was present in 41 (95%) of 43 specimens, 1 had a nonspecific lichenoid reaction, and 1 had lichen simplex; both of the latter had subsequent biopsies showing LS. Lichen planus was not seen in association with SCC. Differentiated vulvar intraepithelial neoplasia (dVIN) was present in 38 (88%) of 43 specimens, whereas 1 had acanthosis with altered differentiation and 4 (9%) had no precursor lesion. Differentiated vulvar intraepithelial neoplasia had standard, basaloid, and hypertrophic morphology, superficially resembling erosive LP in 9 (24%) of 38 and hypertrophic LP in 6 (16%) of 38. Conclusions: Lichen planus was not seen in association with HPV-independent vulvar SCC, whereas LS was underrecognized and inadequately treated in this group. Pathologists should be aware that dVIN may superficially resemble erosive or hypertrophic LP.